2017
DOI: 10.7759/cureus.1894
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic Dilemma: Cerebellopontine Angle Lipoma Versus Dermoid Cyst

Abstract: Both lipomas and dermoid cysts of the cerebellopontine angle are rare tumors. These tumors differ in their embryological origin but share similar features on imaging. Both of these congenital lesions can be found in the cerebellopontine angle (CPA), and symptomatic clinical presentation is dictated by the location of the lesion. This paper demonstrates a unique case in which a CPA lipoma was misidentified as a dermoid cyst, leading to surgical intervention. Further, the paper provides a literature review of CP… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 27 publications
0
9
0
1
Order By: Relevance
“…This study found that conservative, nonoperative management of CPA/IAC lipoma has become increasingly more common and is associated with significantly reduced morbidity as compared to operative management. Lipomas of the CPA/IAC are extremely rare, with only 96 manuscripts reporting 202 CPA/IAC Lipomas prior to this study, and create a diagnostic dilemma for the surgeon, as these lesions may be mistaken for other, more common tumors of the CPA/IAC—for example, vestibular schwannomas, epidermoid cysts, meningiomas, arachnoid cysts, dermoid cysts, and hemangiomas 3,11 . Although lipomas characteristically appear as hypodense masses on computed tomography (CT) imaging, magnetic resonance imaging (MRI) enables improved evaluation of the mass for more accurate diagnostic assessment 12–14 .…”
Section: Discussionmentioning
confidence: 99%
“…This study found that conservative, nonoperative management of CPA/IAC lipoma has become increasingly more common and is associated with significantly reduced morbidity as compared to operative management. Lipomas of the CPA/IAC are extremely rare, with only 96 manuscripts reporting 202 CPA/IAC Lipomas prior to this study, and create a diagnostic dilemma for the surgeon, as these lesions may be mistaken for other, more common tumors of the CPA/IAC—for example, vestibular schwannomas, epidermoid cysts, meningiomas, arachnoid cysts, dermoid cysts, and hemangiomas 3,11 . Although lipomas characteristically appear as hypodense masses on computed tomography (CT) imaging, magnetic resonance imaging (MRI) enables improved evaluation of the mass for more accurate diagnostic assessment 12–14 .…”
Section: Discussionmentioning
confidence: 99%
“… 27 The most common signs of CPA lipomas are hearing loss, tinnitus, vertigo, facial symptoms (facial and trigeminal nerve signs), and headaches. 28 When lipomas are viewed using CT, they appear as hypodense masses (−40 to −100 Hounsfield units [HU]) and do not enhance with contrast administration. 29 On a T1-weighted MRI, lipomas are hyperintense, whereas on T2-weighted sequences, the appearance of a lipoma can vary from hypointense to hyperintense.…”
Section: Discussionmentioning
confidence: 99%
“…Dermoid cysts can remain stable or become symptomatic by enlargement or rupture [4 , 8] . Malignant transformation to squamous cell carcinoma is a rare but a possible complication [9] . The dermoid cyst and epidermoid cyst are different entities, although the term “dermoid” has been used broadly to describe both entities [2] .…”
Section: Discussionmentioning
confidence: 99%
“…Based on such literature, we suspected a lipoma variant or well-differentiated liposarcoma and/or atypical lipomatous tumor preoperatively. Differentiating lipomatous tumors from dermoid cysts is also difficult in the head and neck or in the intracranial location, which are relatively common locations for dermoid cysts [9 , 18] . Bertot et al reported a lipoma at the cerebellopontine angle and indicated that the loss of signal on fat saturation sequences could suggest a lipoma than a dermoid cyst [9] .…”
Section: Discussionmentioning
confidence: 99%